Reliability, usefulness, and validity of a repeated sprint and jump ability test - Buchheit, M.; Spencer, M.; Ahmaidi, S. (International Journal of Sports Physiology and Performance, 2010)
Purpose: Two studies involving 122 handball players were conducted to assess the reliability, usefulness, and validity of a repeated shuttle-sprint and jump ability (RSSJA) test. The test consisted of 6 × (2 × 12.5-m) sprints departing on 25 s, with a countermovement jump performed during recovery between sprints. Methods: For the reliability and usefulness study, 14 well-trained male handball players performed the RSSJA test 7 d apart. Reliability of the test variables was assessed by the typical error of measurement, expressed as a coefficient of variation (CV). The minimal changes likely to be "real" in sprint time and jump power were also calculated. For the validity study, players of seven teams (national to international levels, women and men) performed the RSSJA test. Results: CV values for best and mean sprint time were 1.0% (90% CL, 0.7 to 1.6) and 1.0% (90% CL, 0.7 to 1.4). CV values for best and mean jump peak power were 1.7% (90% CL, 1.2 to 2.7) and 1.5% (90% CL, 1.1 to 2.5). The percent sprint and jump decrements were less reliable, with CVs of 22.3% (90% CL, 15.7 to 38.3) and 34.8% (90% CL, 24.2 to 61.8). Minimal changes likely to be "real" for mean sprint time and jumping peak power were -2.6% and 4.8%. Qualitative analysis revealed that the majority of between-team differences were rated as "almost certain" (ie, 100% probability that the true differences were meaningful) for mean sprint and jump performances. Conclusion: The RSSJA test is reliable and valid to assess repeated explosive effort sequences in team sports such as handball. Test results are likely to be representative of gender and competition level; thus the test could be used to discriminate across playing standards and monitor fitness levels.